2013
DOI: 10.5194/acp-13-11723-2013
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation in particles containing organics mixed with ammonium sulfate, ammonium bisulfate, ammonium nitrate or sodium chloride

Abstract: Abstract. As the relative humidity varies from high to low values in the atmosphere, particles containing organic species and inorganic salts may undergo liquid-liquid phase separation. The majority of the laboratory work on this subject has used ammonium sulfate as the inorganic salt. In the following we studied liquid-liquid phase separation in particles containing organics mixed with the following salts: ammonium sulfate, ammonium bisulfate, ammonium nitrate and sodium chloride. In each experiment one organ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
210
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(241 citation statements)
references
References 97 publications
26
210
5
Order By: Relevance
“…Organic aerosol (OA) often dominates over sulfate (Zhang et al, 2007), in particular in the Southeast in summer where there is a large OA source from biogenic hydrocarbons Marais et al, 2016). Mixing of organic and sulfate aerosol may slow down mass transfer due to phase separation, in which the organic aerosol fraction coats the predominantly aqueous inorganic core, as has been observed in many laboratory studies of organic ammonium sulfate particles (Anttila et al, 2007;Ciobanu et al, 2009;Bertram et al, 2011;Koop et al, 2011;You et al, 2013) as well as in the field in the Southeast (You et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Organic aerosol (OA) often dominates over sulfate (Zhang et al, 2007), in particular in the Southeast in summer where there is a large OA source from biogenic hydrocarbons Marais et al, 2016). Mixing of organic and sulfate aerosol may slow down mass transfer due to phase separation, in which the organic aerosol fraction coats the predominantly aqueous inorganic core, as has been observed in many laboratory studies of organic ammonium sulfate particles (Anttila et al, 2007;Ciobanu et al, 2009;Bertram et al, 2011;Koop et al, 2011;You et al, 2013) as well as in the field in the Southeast (You et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…This results in a particle whose core is predominantly aqueous and inorganic and whose outer shell is predominantly organic. Partially engulfed morphologies are also possible (Song et al, 2012;Veghte et al, 2013). Therefore, ERH for the phase-separated core of such a particle would be close to the ERH of pure ammonium sulfate (Bertram et al, 2011;Buajarern et al, 2007).…”
Section: A Zawadowicz Et Al: Hygroscopic and Phase Separation Prmentioning
confidence: 99%
“…The evidence for liquid-liquid phase separation comes almost solely from microscopy (Bertram et al, 2011;You et al, 2013;Ciobanu et al, 2009) and EDB studies (Marcolli and Krieger, 2006). As a limit of the resolution, the particles studied are large, on the order of 1 µm diameter or greater (Bertram et al, 2011;Ciobanu et al, 2009;Marcolli and Krieger, 2006).…”
Section: A Zawadowicz Et Al: Hygroscopic and Phase Separation Prmentioning
confidence: 99%
“…A number of laboratory studies have focused on liquid-liquid phase separations within particles consisting of inorganic and organic fractions (Svenningsson et al, 2006;Carrico et al, 2008;Dusek et al, 2011;Hodas et al, 2015). For example, studies about liquid-liquid separation occurring in mixed organic-inorganic aerosols were performed by Song et al (2012a, b) and You et al (2013) using Raman and optical microscopy, establishing that liquidliquid phase separation typically occurs in mixed organics + ammonium sulfate (AS) particles with an average elemental oxygen-to-carbon (O : C) ratio of the organic fraction of less than 0.6 and in some cases for 0.6 < O : C < 0.8. You et al (2013) further found that for a O : C ratio between 0.5 and 0.8, the occurrence of liquid-liquid phase separation at a moderate to high RH depends on the types of inorganic salts present (i.e., the effective strength of the salting-out effect), e.g., (NH 4 ) 2 SO 4 ≥ NH 4 HSO 4 ≥ NaCl ≥ NH 4 NO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies about liquid-liquid separation occurring in mixed organic-inorganic aerosols were performed by Song et al (2012a, b) and You et al (2013) using Raman and optical microscopy, establishing that liquidliquid phase separation typically occurs in mixed organics + ammonium sulfate (AS) particles with an average elemental oxygen-to-carbon (O : C) ratio of the organic fraction of less than 0.6 and in some cases for 0.6 < O : C < 0.8. You et al (2013) further found that for a O : C ratio between 0.5 and 0.8, the occurrence of liquid-liquid phase separation at a moderate to high RH depends on the types of inorganic salts present (i.e., the effective strength of the salting-out effect), e.g., (NH 4 ) 2 SO 4 ≥ NH 4 HSO 4 ≥ NaCl ≥ NH 4 NO 3 . Recently, the effect of a potential size-dependent morphology and dependence of the phase separation mechanism on the organic / inorganic mass ratio in mixed aerosol was studied for mixtures of poly(ethylene glycol)-400 + ammonium sulfate using cryogenic-transmission electron microscopy (Altaf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%